#### Answer

$$x = 0$$

#### Work Step by Step

For this problem, we use distributive property first:
$$(4)(x) + (4)(-2) = (2)(x) + (2)(-4) + 3x$$
We multiply the terms:
$$4x - 8 = 2x - 8 + 3x$$
Group like terms on the right side of the equation:
$$4x - 8 = (2x + 3x) - 8$$
Combine like terms:
$$4x - 8 = 5x - 8$$
Subtract $5x$ from each side of the equation to isolate the variable to one side of the equation:
$$-x - 8 = -8$$
Add $8$ to both sides to move the constants to one side:
$$-x = 0$$
Divide both sides by $-1$ to isolate $x$:
$$x = 0$$